Karakteristik aliran dua fase pada saluran ekspansi tiba-tiba - Latif Ngudi Wibawanto; Budi Santoso; Wibawa Endra Juwana (Badan Kerja Sama Teknik Mesin Indonesia, 2016)
This research was conducted to find out the flow characteristic of two phases through the channel with sudden expansion in the form of change of flow pattern and pressure recovery. The test was carried out with variation of superficial velocity of water 0.2-1.3 m / s and superficial air velocity of 0.2-1.9 m / s resulting in pattern of three flow patterns ie bubble, plug, and slug. The expansion channel resulted in some changes to the flow pattern that originally plugs in the upstream channel into bubble in the downstream channel and the slug becomes plug. Pressure recovery experimental results compared with the homogeneous model flow equation and Wadle correlation, both correlations have predictions with standard deviation values of 0.32 and 0.43.